Effects of steam on the reactivity and microstructure of char from in-situ gasification of brown coal - Xu, X.; Wang, Y.; Chen, G.; Chen, Z.; Qin, Z.; Dai, J.; Zhang, Shu; Xu, D. (2015)
©, 2015, Science Press. All right reserved. To examine the effects of steam on the char reactivity and its microstructure, experiments of drying and pyrolysis of brown coal as well as the in-situ gasification of "hot" char were carried out in a newly-designed two-stage reactor. The reactivity and microstructure of in-situ gasification char were characterized by TGA, BET and Raman spectroscopy respectively. The results show that at low temperature of 600?, the steam has little effect on the conversion, reactivity and microstructure of char. When it reaches 700~900?, there are different change trends before and after 2 min of reaction between char and steam. In the first 2 min, the reactivity, the ratio of small aromatic ring systems (3~5 rings) to the large fused rings (=6 rings) and O-containing functional groups decrease dramatically although the char conversion varies little; after 2 min, however, char conversion increases gradually, char reactivity, the ratio of small to big aromatic ring systems and O-containing functional groups decrease slowly. In addition, the pore structure of char follows almost the same variation before and after 2 min. During the first 2 min, a sharp decrease of the ratio of small to big aromatic ring systems and O-containing functional groups are the important factors leading to the decrease of char reactivity; while after 2 min, the change of aromatic ring systems results in the further decrease of char reactivity.